1994
DOI: 10.1006/geno.1994.1390
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor FISH Mapping of YAC Clones in 3p14 and Identification of a YAC Spanning both FRA3B and the t(3;8) Associated with Hereditary Renal Cell Carcinoma

Abstract: Human chromosome band 3p14 contains two tightly linked cytogenetic markers of broad interest, FRA3B and the t(3;8) breakpoint associated with hereditary renal cell carcinoma (RCC). The common fragile site at 3p14.2 (FRA3B) is the most sensitive site on normal human chromosomes to breakage when DNA replication is perturbed by aphidicolin or folate stress. The t(3;8)(p14.2;q24.1) translocation segregates with RCC in a large family and could mark the location of a tumor suppressor gene involved in renal cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…The recently identi®ed FHIT gene encompasses the FRA3B region and the hRCC breakpoint. The hRCC breakpoint and FRA3B are cytologically indistinguishable from each other (Wilke et al, 1994), but detailed molecular analysis with a YAC clone identi®ed by Boldog et al (1993) revealed that the hRCC breakpoint was proximal to both aphidicolin-induced breakpoints generated in a chromosome 3-only somatic cell hybrid (Wang et al, 1993) and a region of consistent breakage observed when lymphocytes were cultured in the presence of aphidicolin (Paradee et al, 1995(Paradee et al, , 1996.…”
Section: Discussionmentioning
confidence: 98%
“…The recently identi®ed FHIT gene encompasses the FRA3B region and the hRCC breakpoint. The hRCC breakpoint and FRA3B are cytologically indistinguishable from each other (Wilke et al, 1994), but detailed molecular analysis with a YAC clone identi®ed by Boldog et al (1993) revealed that the hRCC breakpoint was proximal to both aphidicolin-induced breakpoints generated in a chromosome 3-only somatic cell hybrid (Wang et al, 1993) and a region of consistent breakage observed when lymphocytes were cultured in the presence of aphidicolin (Paradee et al, 1995(Paradee et al, , 1996.…”
Section: Discussionmentioning
confidence: 98%
“…Even though multiple markers which span this breakpoint region have been isolated, a gene has yet to be identi®ed in RCC, with altered expression as a result of the 3;8 rearrangement. One cDNA clone, HCRA1, was identi®ed which mapped adjacent to the 3;8 translocation, but is not rearranged or expressed in RCC patients (Boldog et al, 1993;Wilke et al, 1994). A second gene, FHIT, has been mapped by hybridization to markers from within the t(3;8) RCC breakpoint to the 3p14.2 region.…”
Section: Introductionmentioning
confidence: 99%
“…The expanded FRA16B and FRA10B repeats are highly similar and contain inverted repeats able to form hairpin structures (reviewed in reference 19). Six common fragile sites have been cloned and characterized: FRA3B (3,40,43,58,59,62), FRA7G (24,27), FRA7H (37), FRA16D (34, 45), FRAXB (1), and FRA6F (38). The cytogenetic expression (gaps and constrictions) of these sites is visible along large genomic regions spanning hundreds to thousands of kilobases.…”
mentioning
confidence: 99%